Life cycle environmental and cost evaluation of renewable diesel production. (1st November 2020) - Larnaudie, Valeria; Bule, Mahesh; San, Ka-Yiu; Vadlani, Praveen V.; Mosby, James; Elangovan, S.; Karanjikar, Mukund; Spatari, Sabrina
Graphical abstract: Highlights: Modelling and simulation of renewable diesel production from lignocellulose. Cost analysis for renewable diesel production from biomass sorghum. Preliminary evaluation of environmental metrics using LCA. Abstract: Computer simulations are used to study the production of renewable diesel through the biochemical transformation of biomass sorghum [ Sorghum bicolor (L.) Moench] to free fatty acids using a genetically modified strain of Escherichia Coli . We evaluate select environmental and economic metrics using life cycle assessment (LCA) and techno-economic analysis (TEA). The biofuel supply chain includes feedstock production, handling, pretreatment and hydrolysis, fermentation to free fatty acids, saponification of the free fatty acids, wax production on an electrochemical synthesis reactor, and hydrocracking to convert the wax to renewable diesel. The TEA model developed uses experimental data from pretreatment to wax synthesis steps and literature for the conversion of wax to diesel. The TEA model is integrated into a life cycle inventory model to estimate life cycle greenhouse gas and non-renewable energy consumption. Considering both environmental and economic factors we find that the performance of this pathway to produce renewable diesel returns lower product yield, higher cost, and higher GHG and energy impacts compared to biomass-to-ethanol pathways, primarily due to poor process yields (mainly fermentation). This limitation in the metabolic pathway constrains the maximum yield potential of FFA and therefore renewable diesel and other potential co-products from biomass derived sugars.